Ultrasound assessment of women presented during the first trimester of pregnancy in a rural teaching hospital - Koirala, Sagar; Yadav, Shambhu Kumar; Swarnkar , Kabita Sah; Sanjel , Seshananda (Journal of Karnali Academy of Health Sciences, 2025)
Introduction: First-trimester ultrasound (up to 13 weeks 6 days) is increasingly utilized to verify viability, determine pregnancy age via crown–rump length, identify multiples and chorionicity, and screen for aneuploidy and structural abnormalities. It also aids in diagnosing miscarriage, ectopic pregnancy, and molar pregnancy. Previous research shows differing rates of early pregnancy loss and ectopic pregnancy, highlighting the importance of obtaining local data from Karnali Academy of Health Sciences(KAHS). Methods: A retrospective cross-sectional review involved 451 first-trimester women attending KAHS between January 1 and June 30, 2024. Records with ultrasound reports were included, while incomplete reports were excluded. Data were extracted from the Radiology and Gynecology/Obstetrics outpatient department registries into Excel and analyzed descriptively using SPSS. Ethics approval was obtained from KAHS IRC Ref: 081/082/82. Results: The median age was 24 years (interquartile range 8; range 14–55), with 60.1% aged 20–29. The caste distribution showed the highest group to be Brahmin/Chhetri 66.3%. Ultrasound results showed a viable fetus in 88.25%, retained products of conception in 10.19%, early fetal demise in 0.89%, molar pregnancy in 0.44%, and a blighted ovum in 1 case (0.22%). For viable pregnancies, gestational age was not normally distributed; the median was 7.86 weeks (interquartile range 3.43; range 4–13.43). Gravidity ranged from G1 to G10. Conclusion: First-trimester ultrasound predominantly confirms viable pregnancies while detecting a small share of early losses and rare pathologies, supporting timely early-pregnancy care. These findings align with broader evidence, but comparisons should account for differing denominators and care pathways.